PEMENUHAN HAK ATAS PERLAKUAN YANG SAMA DIHADAPAN HUKUM MELALUI PENYELENGGARAAN BANTUAN HUKUM OLEH PEMERINTAH DAERAH (Fulfilment of Right to Equality Before The Law Providing Legal Aid From Regional Government (Study of Legal Aid in South Sumatera) - Kurnia Saleh (SOL JUSTICIA, 2022)
The right to legal aid is a citizen's constitutional right as a manifestation of the right to equal treatment in the eyes of the law. Law Number 16 of 2011 concerning Legal Aid derives for the regions to be able to allocate the budget for the implementation of Legal Aid in the Regional Revenue and Expenditure Budget (APBD) into Regional Regulations. South Sumatra as one of the provinces that accommodates this mandate through Regional Regulation Number 8 of 2012 concerning Free Legal Aid. This study aimed to examine the basis for providing legal aid to the poor by local governments and the fulfillment of the right to legal aid by local governments. This research will provide guidelines for stakeholders to fulfill the rights of the poor in obtaining access to free legal aid. The normative juridical research method used in this research by conducting a study based on literature studies. The results found in this study indicated that the implementation of legal aid in terms of budgetary availability for legal aid by South Sumatra Provincial Government had not yet been implemented in an applicative manner. Therefore, it needs firmness and commitment from the South Sumatra Provincial Government to implement the provisions in Regional Regulation No. 8 of 2012 concerning Free Legal Aid.